Permanence and Global Attractivity of Discrete Predator-Prey System with Hassell-Varley Type Functional Response. (14th June 2009) - Wu, Runxin; Li, Lin
Abstract : By constructing a suitable Lyapunov function and using the comparison theorem of difference equation, sufficient conditions which ensure the permanence and global attractivity of the discrete predator-prey system with Hassell-Varley type functional response are obtained. Example together with its numerical simulation shows that the main results are verifiable.